Sistem Informasi Pembayaran Iuran Berbasis Mobile pada Kompleks Barokah - Mita Sari Sihaloho; Temi Ardiansah (CV. Keranjang Teknologi Media, 2023)
The process of paying housing dues is still recorded manually using paper, where officers come to residents' homes to collect dues and there are often errors in recording contributions made by residents. This research aims to overcome the problem of building a mobile-based contribution payment information system that can facilitate the process of recording contributions. The results of black box testing to determine the suitability of functions in the decision support system for the determination of healthy cooperatives have a value of 100% in accordance with system functionality testing using black box testing. The results of system testing using ISO 25010 aspects of performance efficiency, aspects of operability, and aspects of functional efficiency obtained a total score of 85.47%. Based on this, ISO 25010 prototype is very good for the application of mobile-based contribution payment information system in the Barokah complex.